Neurodevelopmental and Epilepsy Phenotypes in Individuals With Missense Variants in the Voltage-Sensing and Pore Domains of KCNH5. (7th February 2023) - Happ, Hannah C.; Sadleir, Lynette G.; Zemel, Matthew; de Valles-Ibáñez, Guillem; Hildebrand, Michael S.; McConkie-Rosell, Allyn; McDonald, Marie; May, Halie; Sands, Tristan; Aggarwal, Vimla; Elder, Christopher; Feyma, Timothy; et al.
Abstract : Background and Objectives: KCNH5 encodes the voltage-gated potassium channel EAG2/Kv10.2. We aimed to delineate the neurodevelopmental and epilepsy phenotypic spectrum associated with de novo KCNH5 variants. Methods: We screened 893 individuals with developmental and epileptic encephalopathies for KCNH5 variants using targeted or exome sequencing. Additional individuals with KCNH5 variants were identified through an international collaboration. Clinical history, EEG, and imaging data were analyzed; seizure types and epilepsy syndromes were classified. We included 3 previously published individuals including additional phenotypic details. Results: We report a cohort of 17 patients, including 9 with a recurrent de novo missense variant p.Arg327His, 4 with a recurrent missense variant p.Arg333His, and 4 additional novel missense variants. All variants were located in or near the functionally critical voltage-sensing or pore domains, absent in the general population, and classified as pathogenic or likely pathogenic using the American College of Medical Genetics and Genomics criteria. All individuals presented with epilepsy with a median seizure onset at 6 months. They had a wide range of seizure types, including focal and generalized seizures. Cognitive outcomes ranged from normal intellect to profound impairment. Individuals with the recurrent p.Arg333His variant had a self-limited drug-responsive focal or generalized epilepsy and normal intellect, whereas the recurrent p.Arg327His variant was associated with infantile-onset DEE. Two individuals with variants in the pore domain were more severely affected, with a neonatal-onset movement disorder, early-infantile DEE, profound disability, and childhood death. Discussion: We describe a cohort of 17 individuals with pathogenic or likely pathogenic missense variants in the voltage-sensing and pore domains of Kv10.2, including 14 previously unreported individuals. We present evidence for a putative emerging genotype-phenotype correlation with a spectrum of epilepsy and cognitive outcomes. Overall, we expand the role of EAG proteins in human disease and establish KCNH5 as implicated in a spectrum of neurodevelopmental disorders and epilepsy.